Note. Satisfying Due Dates in Large Job Shops - Hodgson, Thom J.; Cormier, Denis; Weintraub, Alexander J.; Zozom, Andrew (Management Science, 1998)
For the multi-machine job shop scheduling problem, a conceptually simple simulation-based procedure (first proposed by Lawrence and Morton 1986) is shown to be both effective and efficient in providing optimal, or near optimal, schedules for minimizing the maximum lateness, L max . Computational experimentation is used to identify the conditions under which the approach is most viable.